2020
DOI: 10.1002/stab.201900118
|View full text |Cite
|
Sign up to set email alerts
|

Schadensdetektion mithilfe elektromechanischer Impedanzspektren

Abstract: Im Rahmen eines kooperativen Forschungsprojekts der Universität Siegen zwischen der Arbeitsgruppe Technische Mechanik (ATM) des Departments Maschinenbau und des Lehrstuhls Stahlbau und Stahlverbundbau des Departments Bauingenieurwesen wurde eine Methode zur zerstörungsfreien Schadensdetektion an Schrauben und Bolzen entwickelt und auf ihre grundsätzliche Anwendbarkeit hin überprüft. Die Methode basiert auf der Messung von elektromechanischen Impedanzspektren, welche sich bei variierenden Strukturzuständen ände… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…This section contains an overview of similarities and differences with the work of Sahm et al 29 regarding the investigation of bolts used in rail supports. Afterwards, the proposed approach for the damage indicator DI Y ~ true¯ is compared to the commonly used correlation coefficient deviation (CCD) indicator and the root mean square deviation (RMSD) indicator.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This section contains an overview of similarities and differences with the work of Sahm et al 29 regarding the investigation of bolts used in rail supports. Afterwards, the proposed approach for the damage indicator DI Y ~ true¯ is compared to the commonly used correlation coefficient deviation (CCD) indicator and the root mean square deviation (RMSD) indicator.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, estimates are made on the sensitivity of the method. Just as in this work, Sahm et al 29 investigated the monitoring of bolts used in rail supports by observing EMA spectra. Their study consists of preliminary investigations of the effects of varying temperature, varying pretension of the bolt, cuts in the bolt as well as fatigue cracks on the EMA spectra in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lokale Verfahren hingegen basieren oft auf der Ausbreitung von Ultraschall und zeichnen sich durch ein höheres Auflösungsvermögen aus, was eine präzisere Lokalisierung von Schäden ermöglicht [22]. Hierzu zählen u. a. die Schadensdetektion mittels geführter Wellen (Guided Waves) [25][26][27][28][29][30] und die Schadensdetektion mittels elektromechanischer Impedanzen (EMI) [31][32][33][34][35][36][37]. Z s ω ð Þ der Struktur wider.…”
Section: Methoden Zur Detektion Von Korrosionunclassified
“…In addition to the longitudinal and radial modes there are other modes which, however, cause a lower system response in the present case and are therefore not used for evaluation. Investigations have shown that many modes are located in the frequency range bigger/greater than 100 kHz [8]. A determination of the spectrum was made by looking at the individual modes, whereby significant longitudinal and radial modes of the structure are located in the range between 130 kHz and 150 kHz.…”
Section: Definition Of Frequency Sweep Rangementioning
confidence: 99%